Republic of Latvia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
The external imbalances that accompanied Latvia's integration into the global economy have generated mixed effects. Stabilizing net foreign liabilities will require an improvement in the goods and services balance. Outward migration from Latvia has raised concerns about social and economic stresses that could intensify in the near future if labor flow increases. Several steps have to be taken to mitigate any adverse consequences of outward migration. The purpose of this paper is to examine macroeconomic and prudential aspects of the rapid growth of lending in Latvia.